Secure Routing Protocol Using Cross-Layer Design and Energy Harvesting in Wireless Sensor Networks - Nabil Ali Alrajeh; Shafiullah Khan; Jaime Lloret; Jonathan Loo (International Journal of Distributed Sensor Networks, 2013)
Energy efficiency is the main concern of research community while designing routing protocols for wireless sensor networks (WSNs). This concern can be addressed by using energy-harvesting scheme in routing protocols. In this paper, we propose a secure routing protocol that is based on cross layer design and energy-harvesting mechanism. It uses a distributed cluster-based security mechanism. In the cross-layer design, parameters are exchanged between different layers to ensure efficient use of energy. Energy-harvesting system is used to extract and store energy, which is used to take decisions for the node state and thus for the routing issues. Simulation results show that our routing protocol can perform better in many scenarios and in hostile attack-prone environment.